Comparison of dye-sensitized solar cell power output using anthocyanin from eggplant skins (Solanum melongena) and chlorophyll from calamansi leaves (Citrus microcarps) as natural dye-sentisizers. - Pingcas, Charmine Ramos (2011.)
Dye-sensitized solar cells (DSSCs) are widely studied and applied nowadays due to its efficiency in converting light energy, its low-cost production and its being environmentally benign. In this study, dye-sensitized solar cells were fabricated using natural dyes extracted from eggplant skins (Solanum nelongena) and calamansi (Citrus microcarpa) leaves as sensitizers for TiO2 films., The light absorption of the aqueous dye solutions was measured using UV-VIS Spectrophotometer (Sunny UV-7882PCprint). Anthocyanin extract showed a maximum absorbance at 450-452nm while chlorophyll extract at 663nm. The photocurrent and voltage of the cells was measured under direct sunlight and simulated lights, using 20W and 50W halogen lamps. The maximum power output of the chlorophyll-DSSC was 4.4W, 0.3W and 2.1W for the irradiation under direct sunlight, 20W and 50W halogen lamps respectively. anthocyanin-DSSCs power output were 6.6W, 3.1 and 5.4W for the irradiation under direct sunlight, 20W and 50W halogen lamps respectively. Results from the comparison of the DSSCs power output showed that the performance of anthocyanin-DSSC showed much potential as natural dye-sensitizer for solar cells compared to that of the chlorophyll. Thus, the use of anthocyanin for DSSC could be utilized as a sentisizer for solar cells.
Thesis (Undergraduate, Bachelor of Science in Chemistry) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Dye -- Eggplant Skins; Leaves -- Calamansi